Interactive Effects of Morphine on HIV Infection: Role in HIV-Associated Neurocognitive Disorder - Pichili Vijaya Bhaskar Reddy; Sudheesh Pilakka-Kanthikeel; Shailendra K. Saxena; Zainulabedin Saiyed; Madhavan P. N. Nair (AIDS Research and Treatment, 2012)
HIV epidemic continues to be a severe public health problem and concern within USA and across the globe with about 33 million people infected with HIV. The frequency of drug abuse among HIV infected patients is rapidly increasing and is another major issue since injection drug users are at a greater risk of developing HIV associated neurocognitive dysfunctions compared to non-drug users infected with HIV. Brain is a major target for many of the recreational drugs and HIV. Evidences suggest that opiate drug abuse is a risk factor in HIV infection, neural dysfunction and progression to AIDS. The information available on the role of morphine as a cofactor in the neuropathogenesis of HIV is scanty. This review summarizes the results that help in understanding the role of morphine use in HIV infection and neural dysfunction. Studies show that morphine enhances HIV-1 infection by suppressing IL-8, downregulating chemokines with reciprocal upregulation of HIV coreceptors. Morphine also activates MAPK signaling and downregulates cAMP response element-binding protein (CREB). Better understanding on the role of morphine in HIV infection and mechanisms through which morphine mediates its effects may help in devising novel therapeutic strategies against HIV-1 infection in opiate using HIV-infected population.